Pengaruh Citra Merk Dan Komunikasi Dari Mulut ke Mulut Terhadap Keputusan Pembelian (Studi Pada Toko Perhiasan Emas Cahaya Marrakash Bekasi Utara) - Aini, Syamratul; Rahmawati, Nur Fitri (JAMBIS : Jurnal Administrasi Bisnis, 2025)
The rapid development and competition in the trade sector demand various innovations in product marketing. Companies are expected to continuouslyimprove and adjust their brand image and word of mouth communication in line with consumer desires, particularly in the jewelry sector. The results indicate that brand image (X1) has a positive and significant partial effect on purchase decisions (Y) at Toko Mas Cahaya Marakash Bekasi Utara, accounting for 57.2%. Similarly, word of mouth communication (X2) has a positive and significant partial effect on purchase decisions (Y) at Toko Mas Cahaya Marakash Bekasi Utara, accounting for 72%. Both brand image (X1) and word of mouth communication (X2) together have a positive and significant effect on purchase decisions (Y) at Toko Mas Cahaya Marakash Bekasi Utara, accounting for 74.9%, with the remaining 26.1% influenced by other variables not examined in this study.